Intelligent action : a history of artistic research, aesthetic experience, and artists in academia - Ridlen, Tim (Rutgers University Press, 2024)
"Through archival research and analysis of artworks by Gyorgy Kepes, Allan Kaprow, Mel Bochner, and Suzanne Lacy, among others, Intelligent Action examines how these artists brought alternatives to dominant conceptions of research and knowledge production. The book is organized around specific institutional formations-artistic research centers, proposals, exhibitions on college campuses, and the establishment of new schools or pedagogic programs. Formal and social analysis demonstrate how artists responded to ideas of research, knowledge production, information, and pedagogy. Works discussed were produced between 1958 and 1975, a moment when boundaries between media were breaking down in response to technological, cultural, and generational change. In the context of academia, these artistic practices have taken up the look, feel, or language of various research and teaching practices. In some cases, artists bent to the demands of the cold war research university, while in others, artists developed new modes of practice and pedagogy. Reading these works through their institutional histories, author Tim Ridlem shows how artistic research practices and artistic subjectivity developed in the long 1960s within and alongside academia, transforming the role of artists in the process"-- Provided by publisher.
Machine generated contents note: Introduction 1: The New Academic: Artistic Research at the Center for Advanced Visual Studies 2: Aesthetic Experience: Allan Kaprow, Robert Watts, and George Brecht at Rutgers University 3: Decentering Aesthetic Experience: Art in Process at Finch College 4: The Artist as Researcher: John Baldessari, the Feminist Art Program and Allan Kaprow at CalArts Epilogue Acknowledgements Notes Index.
Keywords: Art -- Research -- United States -- History -- 20th century.; Art -- Study and teaching (Higher) -- United States -- History -- 20th century.; Artists as teachers -- United States.; College teachers -- United States.; Art -- Recherche -- États-Unis -- Histoire -- 20e siècle.; Artistes enseignants -- États-Unis.; ART / History / Contemporary (1945-); EDUCATION / Arts in Education.; ART / General